Regenerative potential of allogeneic adipose tissue-derived mesenchymal cells in canine cutaneous wounds - Enciso, Nathaly (2020)
BackgroundMesenchymal stem cells (MSCs) have generated a great amount of interest over the past decade as a novel therapeutic treatment for a variety of diseases. Emerging studies have indicated that MSCs could enhance the repair of injured skin in canine cutaneous wounds.Case presentationA healthy 2 years old Bodeguero Andaluz dog was presented with multiple skin bite wounds. Antibiotic and anti-inflammatory therapy was administered for 8 days. On day three, 10(7) allogeneic adipose-derived mesenchymal stem cells (ASCs) were intradermally injected approximately equidistant to the ASCs treated wounds. Control wounds underwent conventional treatment with a topical antibacterial ointment until wound healing and closure. Wounds, skin morphology and healing progress were monitored via serial photographs and histopathology of biopsies obtained at day seven after ASC treatment. Histopathology revealed absence of inflammatory infiltrates and presence of multiple hair follicles in contrast to the non-ASCs treated control wounds indicating that ASC treatment promoted epidermal and dermal regeneration. ASCs were identified by flow cytometry and RT-PCR. The immunomodulatory role of ASCs was evidenced by coculturing peripheral blood mononuclear cells with allogeneic ASCs. Phytohemagglutinin was administered to stimulate lymphocyte proliferation. Cells were harvested and stained with an anticanine CD3-FITC antibody. The ASCs inhibited proliferation of T lymphocytes, which was quantified by reduction of carboxyfluorescein succinimidyl ester intensity using flow cytometry.ConclusionsCompared with conventional treatment, wounds treated with ASCs showed a higher regenerative capacity with earlier and faster closure in this dog.